1976
DOI: 10.17730/humo.35.1.a47387941v8g1441
|View full text |Cite
|
Sign up to set email alerts
|

Stake Theory as an Explanatory Device in Navajo Alcoholism Treatment Response

Abstract: The usefulness of "stake in society" theory, a form of transactional theory employed by John J. and Irma Honigmann to explain abandonment of frontier-type norms regarding alcohol use by modern Arctic townsmen, is tested in conjunction with differential response to treatment by a group of 110 Navajo alcoholic men. In a modified usage, "stake" is operationally defined by type. It is postulated that many of the men had suffered initial loss of stake in the context of lack of negative sanctions rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…It has been suggested that low levels of identity with any culture may be related to culturally deviant behavior such as problematic drinking (Ferguson, 1976; May, 1982; Oetting and Beauvais, 1990–1991). Whereas, high identification with at least one culture has been association with more well-being (Phinney, 1989; Oetting and Beauvais, 1990–1991; Moran et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that low levels of identity with any culture may be related to culturally deviant behavior such as problematic drinking (Ferguson, 1976; May, 1982; Oetting and Beauvais, 1990–1991). Whereas, high identification with at least one culture has been association with more well-being (Phinney, 1989; Oetting and Beauvais, 1990–1991; Moran et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring a variety of programs is especially necessary in multicultural regions. For more information on relevant issues in treatment see Institute of Medicine (1989, Chapters 7 through 14), Harding Associates (1988), Kahn and Stephen (1981), Kahn and Fua (1985), Ferguson (1968Ferguson ( , 1970Ferguson ( , 1976, Bach and Bornstein (1981), Westermeyer and Peake (1983), and Glaser (1974).…”
Section: Treatmentmentioning
confidence: 99%
“…Conversely, Ferguson (1976), French and Hornbuckle (1980), and May (1982) have all concluded that the American Indians who are highest risk for substance abuse problems are those who are “marginalized” with respect both to their traditional cultures and to mainstream culture.…”
Section: Use Of Traditional Culture In the Treatment And Prevention Omentioning
confidence: 99%